The microenvironment in breast cancer progression: biology and implications for treatment - Place, Andrew E (BioMed Central, 2011)
Breast cancer comprises a heterogeneous group of malignancies derived from the ductal epithelium. The microenvironment of these cancers is now recognized as a critical participant in tumor progression and therapeutic responses. Recent data demonstrate significant gene expression and epigenetic alterations in cells composing the microenvironment during disease progression, which can be explored as biomarkers and targets for therapy. Indeed, gene expression signatures derived from tumor stroma have been linked to clinical outcomes. There is increasing interest in translating our current understanding of the tumor microenvironment to the development of novel therapies.